The magic handbag - Moss, Stephanie; Moore, Natalia ([Sywell] : Igloo Books, 2021)
Princess Annabelle is ready for a big adventure. When she stumbles across a magical, glowing handbag, will all of her dreams finally come true?
"Join Princess Annabelle for a magical day of adventures!"--Cover.
Keywords: Magic -- Juvenile fiction